X—Why Trust Science? Reliability, Particularity and the Tangle of Science. Issue 3 (7th April 2021) - Cartwright, Nancy
Abstract: In evaluating science, philosophers tends to focus on general laws and on their truth . I urge a shift in focus to the reliability of the panoply of outputs science produces ('the tangle of science') and in tandem, from the general to the particular . Here I give five arguments to support this, including (a) many, many scientific outputs (measures, devices, empirical studies, model organisms, and so on), which must be supposed reliable if we are to warrant our general principles, aren't truth-apt; and (b) reliability invites the crucial question, 'Reliable for what?' Getting clear the particular purpose is essential for effective action and just evaluation.